Challenges in the diagnosis of peripartum cardiomyopathy: a case series. Issue 2 (16th February 2021) - Chirillo, Fabio; Baritussio, Anna; Cucchini, Umberto; Toniolli, Ermanno; Polo, Angela; Iavernaro, Antonio
Abstract: Background: Peripartum cardiomyopathy (PPCM) is usually characterized by overt heart failure, but other clinical scenarios are possible, sometimes making the diagnosis challenging. Case summary: We report a case series of four patients with PPCM. The first patient presented with acute heart failure due to left ventricular (LV) systolic dysfunction. Following medical treatment, LV function recovered completely at 1 month. The second patient had systemic and pulmonary thromboembolism, secondary to severe biventricular dysfunction with biventricular thrombi. The third patient presented with myocardial infarction with non-obstructed coronary arteries and evidence of an aneurysm of the mid-anterolateral LV wall. The fourth patient, diagnosed with PPCM 11 years earlier, presented with sustained ventricular tachycardia. A repeat cardiac magnetic resonance, compared to the previous one performed 11 years earlier, showed an enlarged LV aneurysm in the mid-LV anterolateral wall with worsened global LV function. Discussion: Peripartum cardiomyopathy may have different clinical presentations. Attentive clinical evaluation and multimodality imaging can provide precise diagnostic and prognostic information.